STRATEGI PENGENDALIAN BIAYA SEBAGAI ALAT PERENCANA LABA - Hermawan, Budi (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2010)
Controlling costs is one of the most important element in the management of profit. Controlling costs is an act which was carried out continously to control the costs to be able to generate revenue and profits in accordance with the intended purpose of management. Cost control is good and not always at a low cost. In general the company’s operations, management is always trying to achieve low cost, but it is not entirely correct. In some situations, increased costs may be the best action to improve profits. Management may take a few steps cost control strategies to manage the company in achieving profits, as follow: control by increasing sales; controlling cost of goods sold and gross profit; evaluate the operating costs and focus on the management of profit centers of activity. Kata kunci: Pengendalian, Pendapatan, Biaya, Laba.